SUPERVISI KEPALA SEKOLAH (Upaya Peningkatan Profesionalisme Guru Pada Integrasi Sains Dan Nilai-Nilai Islam) - Abdul Azis (Ulumuna: Jurnal Studi Keilsman, 2018)
The principal has an important role in improving the professionalism of teachers, it is in order that a teacher really has competence is good and getting better. When teachers who teach the professional it will be received well particularly in students learning science and Islamic values, this requires extra power from the other, because it is still integrating the two disciplines. This certainly requires effort conducted by the principal to help teachers to become more professional. From a variety of roles at the top in increasing professionalism of teachers wrong satunnya is the head of school as the supervisor. Supervision is a guidance, coaching, gave his assessment to the educational institutions associated with a management educator and educational management, student management, learning management, curriculum management, financial management, facility management infrastructure, and management services. In addition, the supervision of the head of school may also help the integration of science and Islamic values indirectly.